The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1073/pnas.2002146117
|View full text |Cite
|
Sign up to set email alerts
|

Inner ear sensory system changes as extinct crocodylomorphs transitioned from land to water

Abstract: Major evolutionary transitions, in which animals develop new body plans and adapt to dramatically new habitats and lifestyles, have punctuated the history of life. The origin of cetaceans from land-living mammals is among the most famous of these events. Much earlier, during the Mesozoic Era, many reptile groups also moved from land to water, but these transitions are more poorly understood. We use computed tomography to study changes in the inner ear vestibular system, involved in sensing balance and equilibr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
86
3

Year Published

2020
2020
2021
2021

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 61 publications
(95 citation statements)
references
References 58 publications
4
86
3
Order By: Relevance
“…As was also discussed in Spiekman et al (2020), the geometry of the semicircular canals is correlated to certain aquatic adaptations. Most evidently, the semicircular canals of deep-diving pelagic reptiles are generally short and robust in comparison to terrestrial and nearshore aquatic taxa (Evers et al, 2019;Neenan et al, 2017;Neenan & Scheyer, 2012;Schwab et al, 2020). The comparatively elongate and gracile semicircular canals and common crus of PIMUZ T 2790 are clearly in correspondence to the type observed in terrestrial and nearshore aquatic taxa, and therefore it can be excluded that Tanystropheus hydroides was a deep-diving pelagic animal.…”
Section: Endocranial Anatomymentioning
confidence: 84%
“…As was also discussed in Spiekman et al (2020), the geometry of the semicircular canals is correlated to certain aquatic adaptations. Most evidently, the semicircular canals of deep-diving pelagic reptiles are generally short and robust in comparison to terrestrial and nearshore aquatic taxa (Evers et al, 2019;Neenan et al, 2017;Neenan & Scheyer, 2012;Schwab et al, 2020). The comparatively elongate and gracile semicircular canals and common crus of PIMUZ T 2790 are clearly in correspondence to the type observed in terrestrial and nearshore aquatic taxa, and therefore it can be excluded that Tanystropheus hydroides was a deep-diving pelagic animal.…”
Section: Endocranial Anatomymentioning
confidence: 84%
“…For example, using anatomical network analysis, Fernández et al (2020) found that there are two main mechanisms by which secondarily aquatic tetrapods form fins from limbs: persistence of interdigital and superficial connective tissues (seen in mosasaurs and plesiosaurs), and reintegration of the digits with the mesopodium (seen in ichthyosaurs). Additionally, Schwab et al (2020) found that, in the evolution of thalattosuchians, a lineage of fully aquatic crocodylomorphs, the inner ear labyrinth became more thick and compact gradually; this is different from cetaceans, which evolved relatively small inner ear labyrinths very quickly, and suggests that the semiaquatic phase of thalattosuchian evolution lasted longer than that of cetaceans. The advantage of comparing these and other features associated with an aquatic lifestyle (e.g., shortening of long bones, nostril retraction, increase in orbit size) across lineages and in an ontogenetic context is that it can identify the heterochronic processes that drove each transition and determine whether each instance is novel or convergent with respect to fundamental developmental mechanisms.…”
Section: Discussionmentioning
confidence: 98%
“…They suggest that other constraints, such as visual acuity, head size, and spatial constraints within the cranium could instead determine the major variation associated with labyrinth shape 42 . Some studies have reported potential aquatic adaptations to the endosseous labyrinth in non-dinosaurian reptiles 30,[55][56][57] . However, the hypothesis that aquatic tetrapods have low aspect ratios (i.e.…”
Section: Vestibular Anatomy As a Guide To Ecological Reconstructions?mentioning
confidence: 99%
“…comparatively dorsoventrally low and anteroposteriorly long labyrinths 55 ;) is not supported by more recently collected data 30 . Additionally, thick endosseous semicircular canals, although found in several secondarily marine groups 30,56,57 , can also be present in highly terrestrial animals 30 . Furthermore, the endosseous labyrinths of phylogenetically shallow marine lineages, such as penguins or seals seem to be influenced more strongly by other factors like phylogeny (penguins: 55,56 ; neodiapsids: 58 ), or neck agility (seals: 59 ), rather than habitat ecology.…”
Section: Vestibular Anatomy As a Guide To Ecological Reconstructions?mentioning
confidence: 99%